The Dynamics of Communication Between the Regional People's Representative Council and Regional Apparatus Organizations in Fighting for the Interests - Arpiah, Arpiah; Yusmanizar, Yusmanizar; Sukmarini, Andi Vita (Journal La Sociale, 2026)
This research aims to determine the dynamics of communication between the Regional People's Representative Council (DPRD) and Regional Apparatus Organizations (OPD) in advocating for the interests of the people of Nunukan Regency and the factors that influence it. This research was conducted at the Nunukan Regency DPRD office, the offices of the Nunukan Regency Government OPDs, and the homes of DPRD members who served as informants. Data collection was conducted through in-depth interviews, participant observation, and the use of supporting documents. The results of this reserach indicate that communication between the two institutions generally begins with an official letter and continues with informal communication using telephone or WhatsApp as needed. The content of the messages conveyed during the communication process is influenced by the problems being faced. The communication patterns used is to apply persuasive, coercive, and informative communication techniques according to the situation and conditions during the communication process. The result of this research also shows that factors that hinder smooth communication are the emergence of fear, worry, suspicion, pressure, the presence of parties who feel they have a higher status, limited time when communicating, differences in background, inability to understand the situation of the interlocutor, lack of mastery of applicable regulations, and the use of technical and foreign terms that are difficult for the interlocutor to understand.